1989
DOI: 10.1161/01.res.65.6.1526
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex control of renal sympathetic nerve activity is preserved in heart failure despite reduced arterial baroreceptor sensitivity.

Abstract: The purpose of this study was to determine if arterial baroreflex control of sympathetic nerve traffic is impaired in heart failure. We recorded renal nerve activity during changes in arterial pressure while simultaneously recording from aortic baroreceptor afferent fibers in 10 dogs with heart failure induced by rapid ventricular pacing and in 10 sham animals. Sensitivity of the aortic baroreceptors (percent change in nerve activity per millimeters mercury change in mean arterial pressure) was reduced in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 38 publications
6
57
1
Order By: Relevance
“…30,[32][33][34][35] Our results were compatible with these reports. The precise mechanism of reduced BRS was studied in animals with experimental heart failure, and it was shown that, in addition to reduced sensitivity of the baroreceptors themselves, a decrease in the reactivity of vagal afferents, sympathetic efferents, and peripheral effectors was also responsible for impairment of this reflex arc, but most authors have found an association of reduced BRS with decreased vagal afferent neural activity.…”
Section: Relationship Between Brs and Humoral Factors In Heart Failuresupporting
confidence: 93%
See 1 more Smart Citation
“…30,[32][33][34][35] Our results were compatible with these reports. The precise mechanism of reduced BRS was studied in animals with experimental heart failure, and it was shown that, in addition to reduced sensitivity of the baroreceptors themselves, a decrease in the reactivity of vagal afferents, sympathetic efferents, and peripheral effectors was also responsible for impairment of this reflex arc, but most authors have found an association of reduced BRS with decreased vagal afferent neural activity.…”
Section: Relationship Between Brs and Humoral Factors In Heart Failuresupporting
confidence: 93%
“…The precise mechanism of reduced BRS was studied in animals with experimental heart failure, and it was shown that, in addition to reduced sensitivity of the baroreceptors themselves, a decrease in the reactivity of vagal afferents, sympathetic efferents, and peripheral effectors was also responsible for impairment of this reflex arc, but most authors have found an association of reduced BRS with decreased vagal afferent neural activity. [29][30][31][32]36 This abnormality of BRS in heart failure has been thought to be functional rather than organic because heart transplantation 34 and the control of heart failure 35 improved BRS. In the present study, we found no significant correlation between a decrease of BRS and overactivation of sympathetic nervous system, but a direct relationship was observed between a low BRS and an increased ANP level.…”
Section: Relationship Between Brs and Humoral Factors In Heart Failurementioning
confidence: 99%
“…The normal control of CSNA by the arterial baroref lex indicates that the impaired response of HR must be because of depressed parasympathetic control, as described (26,27). Studies in humans (28,29) and animal models of HF (30,31) support the concept that the arterial baroref lex control of SNA is not altered in HF. However, there is evidence from studies in rabbits that the baroref lex control of RSNA is desensitized in HF (24,25,32).…”
Section: Discussionmentioning
confidence: 87%
“…Although all animal models have limitations, the animal model of pacing-induced HF has been used extensively and shows the symptoms of HF seen clinically, including decreased ventricular function and intense neurohumoral activation (30,33). Importantly, the level of neurohumoral activation in pacing models of HF closely parallels that seen in human HF patient populations (34).…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence suggesting that arterial baroreceptor-mediated control and cardiopulmonary receptor-mediated control are altered in both human [10][11][12][13] and experimental heart failure, [14][15][16] but there are few studies concerning the compensatory process after acute left ventricular overloading. We previously demonstrated that left ventricular function progressively deteriorated, along with myocardial -adrenergic receptor down-regulation, depletion of catecholamines and an increase in plasma norepinephrine level, during the first week after production of aortic regurgitation (AR) in rabbits.…”
mentioning
confidence: 99%